Natural products: Potential lead compounds for the treatment of endometriosis. (February 2020) - Machairiotis, Nikolaos; Vasilakaki, Sofia; Kouroutou, Paraskevi
Abstract: Objective: Medical plants have been used for centuries for the treatment of various disorders in humans and animals. The therapeutic properties of herbs and plants have been documented for years, giving rise to ethnobotany, and have been a source for the development of novel drugs. Natural products usually have more than one pharmaceutical effects, due to the fact that they interact with more than one biological targets. This property could be used for the efficient treatment of diseases with multiple putative physiopathologic mechanisms, such as endometriosis. Study design: In the current study, we search the literature to find recent progress in the identification of compounds, which derived from plants and herbs and have therapeutic properties against endometriosis and its symptoms. The Scopus and PubMed databases were used to search for original articles, published between January 2018 and July 2019. The words "endometriosis", "pain", "treatment", "medication" were used for the query. Results and conclusion: 14 compounds derived from plants and herbs have demonstrated pharmaceutical activity in experiments, including animal models and human endometriotic samples. The experimental data evidence the therapeutic effect of several natural products against endometriosis. Given that most of them are already well known for their pharmaceutical properties, these compounds should be used as leads for the development of novel drugs for the treatment of endometriosis.